A STUDY ON RELATIOSHIP BETWEEN INTERNAL BRANDING AND EMPLOYEE AFFECTIVE COMMITMENT IN BANKING SECTOR - Dr.Sowmiya.M; Dr.K.Priya; Dr. D.K.Hemamalini (The Bioscan, 2024)
The necessity to have an efficient staff is essential to the organizational objectives. Employee commitment has constantly been a prominent aspect of inquiry due to its predictive potential in light of the growing realization that employees' emotional bonds to their organizations seem to be an important predictor to dedication and loyalty. The goal of this study is to determine how internal branding can increase employee affective commitment. The survey research design technique was employed. The method of survey research design was used. The study examined the 4 private banks with a combined workforce of 134 employees were chosen as the sample items out of the total using the simple random sampling technique. A structured 30-item questionnaire that had been validated served as the research tool.